Drug Screening Identifies Sigma-1-Receptor as a Target for the Therapy of VWM Leukodystrophy - Atzmon, Andrea; Herrero, Melisa; Sharet-Eshed, Reut; Gilad, Yocheved; Senderowitz, Hanoch; Elroy-Stein, Orna (Frontiers in Molecular Neuroscience, 2018)
Vanishing White Matter (VWM) disease is an autosomal genetic leukodystrophy caused by mutations in subunits of eukaryotic translation initiation factor 2B (eIF2B). The clinical symptoms exhibit progressive loss of white matter in both hemispheres of the brain, accompanied by motor functions deterioration, neurological deficits and early death. To date there is no treatment for VWM disease. The aim of this work was to expedite rational development of a therapeutic opportunity. Our approach was to design computer-aided strategy for an efficient and reliable screening of drug-like molecules; and to use primary cultures of fibroblasts isolated from the Eif2b5R132H/R132H VWM mouse model for screening. The abnormal mitochondria content phenotype of the mutant cells was chosen as a read-out for a simple cell-based fluorescent assay to assess the effect of the tested compounds. We obtained a hit rate of 0.04% (20 hits out of 50,000 compounds from the selected library). All primary hits decreased mitochondria content and brought it closer to WT levels. Structural similarities between our primary hits and other compounds with known targets allowed the identification of three putative cellular pathways/targets: 11-HSD1, Sonic hedgehog (Shh), and Sigma-1-Receptor (S1R). In addition to initial experimental indication of Shh pathway impairment in VWM mouse brains, the current study provides evidence that S1R is a relevant target for pharmaceutical intervention for potential treatment of the disease. Specifically, we found lower expression level of S1R protein in fibroblasts, astrocytes and whole brains isolated from Eif2b5R132H/R132H compared to WT mice, and confirmed that one of the hits is a direct binder of S1R, acting as agonist. Furthermore, we provide evidence that treatment of mutant mouse fibroblasts and astrocytes with various S1R agonists corrects the functional impairments of their mitochondria and prevent their need to increase their mitochondria content for compensation purposes. Moreover, S1R activation enhances the survival rate of mutant cells under ER-stress conditions, bringing it to WT levels. This study marks S1R as a target for drug development towards treatment of VWM disease. Moreover, it further establishes the important connection between white matter well-being and S1R-mediated proper mitochondria/ER function.